2017
DOI: 10.1021/jacs.7b06186
|View full text |Cite
|
Sign up to set email alerts
|

Structures and Mechanisms of the Non-Heme Fe(II)- and 2-Oxoglutarate-Dependent Ethylene-Forming Enzyme: Substrate Binding Creates a Twist

Abstract: The ethylene-forming enzyme (EFE) from Pseudomonas syringae pv. phaseolicola PK2 is a member of the mononuclear non-heme Fe(II)- and 2-oxoglutarate (2OG)-dependent oxygenase superfamily. EFE converts 2OG into ethylene plus three CO2 molecules while also catalyzing the C5 hydroxylation of L-arginine (L-Arg) driven by the oxidative decarboxylation of 2OG to form succinate and CO2. Here we report eleven X-ray crystal structures of EFE that provide insight into the mechanisms of these two reactions. Binding of 2OG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
146
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(156 citation statements)
references
References 42 publications
7
146
1
Order By: Relevance
“…For example, this is indeed observed in the crystal structure coordinates of, for example, taurine/α‐ketoglutarate dioxygenase (TauD), α‐ketoglutarate‐dependent leucine 5‐hydroxylase (GriE), and 2‐(trimethylammonio) ethylphosphonate hydroxylase (TmpA) . In the ethylene‐forming enzyme (EFE), interestingly, the position of this Arg residue has shifted to a closer position to the axial histidine group in the protein chain and we find a HX 8 R motif in the pdb file . In addition, the structure of EFE shows a second Arg residue within hydrogen‐bonding distance to the terminal carboxylate group of αKG in the substrate‐bound pdb file, namely Arg 171 .…”
Section: Second‐coordination Sphere Effects In Nonheme Iron Enzymesmentioning
confidence: 83%
See 1 more Smart Citation
“…For example, this is indeed observed in the crystal structure coordinates of, for example, taurine/α‐ketoglutarate dioxygenase (TauD), α‐ketoglutarate‐dependent leucine 5‐hydroxylase (GriE), and 2‐(trimethylammonio) ethylphosphonate hydroxylase (TmpA) . In the ethylene‐forming enzyme (EFE), interestingly, the position of this Arg residue has shifted to a closer position to the axial histidine group in the protein chain and we find a HX 8 R motif in the pdb file . In addition, the structure of EFE shows a second Arg residue within hydrogen‐bonding distance to the terminal carboxylate group of αKG in the substrate‐bound pdb file, namely Arg 171 .…”
Section: Second‐coordination Sphere Effects In Nonheme Iron Enzymesmentioning
confidence: 83%
“…To highlight the difference in the αKG position in the protein structure of EFE compared with alternative nonheme iron/αKG dependent dioxygenases, we created an overlay of the crystal structure coordinates of TauD (1OS7 pdb file) and EFE (5V2Y pdb file), see Figure . Both structures have the typical 2‐His/1‐Asp facial ligand motif and we created an overlay of these first‐coordination sphere ligands of the two proteins in roughly the same position.…”
Section: Second‐coordination Sphere Effects In Nonheme Iron Enzymesmentioning
confidence: 99%
“…Alternate reaction outcomes are believed to diverge post HAT by the ferryl intermediate via redirection of the substrate radical. Characterization of bacterial Fe/2OGs catalyzing halogenation, epimerization, and desaturation have helped reveal some of these underlying mechanistic controls (Blasiak et al, 2006;Chang et al, 2014;Mitchell et al, 2016;Martinez et al, 2017;Dunham et al, 2018). Another notion gaining support for avoidance of a hydroxylation outcome is the relocation of the ferryl intermediate to a more distal coordination site, sacrificing HAT efficiency but favoring (Mitchell et al, 2016;Srnec et al, 2016;Martinie et al, 2017;Mitchell et al, 2017b).…”
Section: Fe/2ogsmentioning
confidence: 99%
“…HAT from C2 by an Fe(IV)-oxo species is believed to initiate breakdown to ethylene and cyanoformate, the latter of which is shunted away from the active site before it decomposes (Murphy et al, 2014). Interestingly, bacteria also use an Fe/2OG-like enzyme for ethylene production, known as the ethylene-forming enzyme, which directly oxidizes the iron-bound 2OG molecule to ethylene and two molecules of CO 2 (Martinez and Hausinger, 2016;Martinez et al, 2017;Zhang et al, 2017). Ethylene-forming enzymes have garnered much interest as a sustainable source for bioethylene production, as their 2OG substrate is cheap and it does not produce a toxic by-product like cyanide compared with ACCO.…”
Section: Aminocyclopropanecarboxylate Oxidasementioning
confidence: 99%
“…It was further suggested that three water molecules occupy three iron-binding sites in the resting state of enzyme to give an octahedral geometry of the iron center. For all the structural and spectroscopic characterized Fe/αKG enzymes, αKG forms a bidentate binding to the iron center by replacing two of the three water molecules, and the primary substrate binds in the vicinity of the iron center (an exception is αKG ethylene-forming enzyme (EFE), where in one of the reported crystal structures, a mono-dentate binding of αKG is proposed [ 74 ]). Model chemistry studies on mimicking the structures of the ferrous and the ferryl state of enzymes also greatly enhanced our understandings on Fe/αKG enzymes [ 5,75 ].…”
mentioning
confidence: 99%